Noninvasive estimation of the pressure profile in the male urethra using ultrasound imaging. Issue 4 (18th March 2015) - Idzenga, Tim; Arif, Muhammad; van Mastrigt, Ron; de Korte, Chris L.
Abstract : Purpose: Decreased prostatic compliance as a result of benign prostatic enlargement can result in bladder outlet obstruction. This changes the urethral pressure profile during voiding. In this study, the authors propose noninvasive estimation of this pressure profile. In four soft tissue mimicking models of the urethra with increasing degree of obstruction, the authors measured deformation of the wall during flow, using ultrasound imaging. Combined with estimates of the model compliance, the authors were able to estimate the pressure profile. Methods: First, the compliances (Young's moduli) of the four models were derived by applying static luminal pressure and measuring the resulting strain of the tissue using an ultrasound imaging system. Next, continuous flow was applied to the models and the strain in the urethral wall was measured similarly. The luminal pressure profile was estimated from the strain (measured under continuous flow conditions) and the derived compliance (measured under static pressure conditions). The estimated pressures up‐ and downstream of the obstruction were compared with the corresponding measured pressures. In the obstructed region, the strain gradient was estimated using linear regression. Results: The luminal pressure values estimated from the ultrasound data up‐ and downstream of the obstruction were not significantly different from the corresponding measured pressures. The general pressure profile showed a decrease along the length of the obstruction followed by a small increase after the obstruction. The strain gradient in the obstructed region reflected the decrease in urethral pressure and increased with flow rate and degree of obstruction. Conclusions: The results from this model study illustrate the feasibility of noninvasive estimation of the urethral pressure profile using ultrasound. This offers the prospect of a noninvasive, ultrasound based diagnostic tool for assessment of bladder outlet obstruction in men with lower urinary tract symptoms.